THE IMPACT OF CROP YEAR AND A FEW AGROTECHNICAL ELEMENTS ON THE FATTY ACID COMPOSITION OF LO AND HO SUNFLOWER (HELIANTHUS ANNUUS L.) OIL - Péter Pepó; Adrienn Novák (Journal of Animal and Plant Sciences, 2017)
The fatty acid composition of seven sunflower (Helianthus annuus L.) hybrids of different genotypes (LO = normal, linoleic acid, HO = high oleic acid) was examined in two different crop years (2012 and 2013) in Eastern Hungary (North latitude: 47o5’ East longitude: 21o4’) on calcareous chernozem soil. Genotypes, sowing dates and fungicide using were studied in small-plot experiment. The linoleic acid content of LO hybrids was between 44.5-61.0%, that of HO hybrids ranged between 2.2-14.0%, while their respective oleic acid content varied between 24.2-45.2% and 82.2-90.9%, depending on genotype and crop year. The impact of sowing date and fungicide treatment was moderate and insignificant in the majority treatments. The oleic acid content of HO hybrids showed significant differences in both years depending on genotype (88.6-90.3% in 2012 and 82.2-90.9% in 2013). There was a close negative correlation between the linoleic acid and oleic acid content of LO and HO hybrids (LO hybrids: -0.994** – -0.918**, HO hybrids -0.996** – -0.995**) in both crop years.In the experiment without isolation, the oleic acid content of HO hybrids was constantly above 80% in both years.
Keywords: genotype; saturated and non saturated fatty acids; sowing date; fungicide